2019
DOI: 10.3349/ymj.2019.60.6.592
|View full text |Cite
|
Sign up to set email alerts
|

Higher Fatality for Severe Fever with Thrombocytopenia Syndrome Complicated by Hemophagocytic Lymphohistiocytosis

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious zoonosis caused by the SFTS virus. Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening syndrome associated with excessive immune activation. Cytokine storms are often seen in both SFTS and HLH, resulting in rapid disease progression and poor prognosis. The aim of this study was to identify whether SFTS cases complicated by HLH are related to higher rates of mortality. Descriptive analysis of the frequency of clinical and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“… 4 Jung et al suggested SFTS cases complicated by HLH have a worse prognosis. 27 In our data, bone marrow aspirate was performed in 23 patients. Heteromorphic lymphocyte can be found in more than half of surviving patients.…”
Section: Discussionmentioning
confidence: 95%
“… 4 Jung et al suggested SFTS cases complicated by HLH have a worse prognosis. 27 In our data, bone marrow aspirate was performed in 23 patients. Heteromorphic lymphocyte can be found in more than half of surviving patients.…”
Section: Discussionmentioning
confidence: 95%
“…The underlying mechanism had been posed from other viruses such as influenza virus or HIV, where infected monocytes could initiate hyper-coagulation and severely decrease the clotting time (Bouwman et al, 2002;Wilson et al, 2014). It is strongly postulated that SFTSV-activated monocytes in part trigger systemic inflammatory response syndrome (SIRS) in severe/fatal cases, and they play a critical role in inducing coagulation abnormalities, even hemophagocytic lymphohistiocytosis (HLH), the complication of which had been disclosed from autopsy pathology of fatal SFTS and clinical series (Jung et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the advanced age of the affected patient, hemophagocytic lymphohistiocytosis (HLH) and central nervous symptoms have also been found to be associated with fatal outcomes. Further, an association between fatal cases of SFTS and HLH was described in another study 54 , 55 , although only a small number of cases were reported. HLH is an immune-mediated life-threatening syndrome associated with excessive immune activation 56 .…”
Section: Clinical Characteristics In Sfts Patientsmentioning
confidence: 92%